Analysis of Adhesion of Yersinia pestis Vaccine Strain EV to Erythrocytes of the Animals Using Photocolorimetric Method - V. A. Oborin; E. V. Pimenov; A. G. Ivonin (Проблемы особо опасных инфекций, 2010)
The adhesive properties of Y. pestis vaccine strain EV as regards the erythrocytes of laboratory, domestic and agricultural animals were studied using photocolorimetric method. The level of bacteria adhesion was shown to depend upon erythrocytes species as well as upon incubation conditions of bacterial and eukaryotic cells. The received data suggested interaction of erythrocytes and Y. pestis to be significant in the development of infectious process caused by plague agent.